Media Cici Drama dalam Pembelajaran Teks Drama Kelas VIII (SATU Press Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2021)
Drama learning in grade VIII of Junior High School obtains several problems. These problems include students who are less active in participating in learning, intake of students in understanding drama material is low, and the learning media used are less varied. Therefore, teacher creativity is really needed, especially in presenting interesting and effective learning media. Based on that, this article is to study the media design for drama texts learning called